2015
DOI: 10.1111/rego.12092
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of rigorous and credible transnational governance: A cross‐sectoral analysis of best practice compliance in eco‐labeling

Abstract: The number of eco‐labeling schemes is rising dramatically, yet the rigor and credibility of such schemes remains uneven. Whereas some eco‐labeling organizations (ELOs) comply with best practice guidelines designed to increase the credibility of their standards through attention to good operating principles, such as transparency and impartiality, others do not. Within this article, I attempt to explain this variation through multivariate regression analysis of an original cross‐sectoral dataset of transnational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 59 publications
1
23
1
Order By: Relevance
“…Interestingly, NGO involvement does not have the same effect. Our data does not point to a statistically significant relationship between NGO involvement and greater transparency (Grigorescu 2007;Abbott & Snidal 2009a;van der Ven 2015). Various explanations are possible for the absence of an "NGO effect."…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, NGO involvement does not have the same effect. Our data does not point to a statistically significant relationship between NGO involvement and greater transparency (Grigorescu 2007;Abbott & Snidal 2009a;van der Ven 2015). Various explanations are possible for the absence of an "NGO effect."…”
Section: Discussioncontrasting
confidence: 82%
“…Cashore et al described them as "one of the most innovative and startling institutional designs of the past 50 years" (2004, p. 298). Several authors have also drawn a direct connection between the inclusion of NGOs and transparency (Florini 2002;Grigorescu 2007;Gulbrandsen 2008;van der Ven 2015). On the one hand, they describe a "normative mechanism."…”
Section: Internal Determinants 411 Involvement Of Non-governmentalmentioning
confidence: 99%
“…1 In contrast, the commitment approach, developed and favored by many NGO-led PRIs, involves more rigorous standards, acquiring an indepth knowledge of conditions in factories through intensive factory monitoring, as well as significant engagement with local factories, unions, and NGOs. 2 The compliance approach is considered to be less stringent than the commitment approach, meaning that it is less comprehensive in terms of the number of issues covered and less prescriptive in terms of mandatory and substantive thresholds (Bernstein & Cashore 2007;Fransen & Burgoon 2011;van der Ven 2015). 3 However, as it shifts demands and costs from the buyers to the suppliers, it is generally favored by larger retailers who deal with large numbers of suppliers (Fransen 2011;Fransen & Burgoon 2011;Marques 2016;Sum 2010).…”
Section: Empirical Setting and Backgroundmentioning
confidence: 99%
“…Some might perceive this as a conflict of interest, since the MSC stands to financially benefit from making its eco‐label more easily achievable and licensable. Others counter that there are procedural safeguards in place to prevent this from happening (van der Ven, ). In either case, there is some degree of incentive to create easily achievable standards and overlooking noncompliance issues in order to profit from certification and labeling activities (Cashore, Auld, Bernstein, & McDermott, ; Mayer & Gereffi, ).…”
Section: Novel Ethical Considerations For Gvc Membersmentioning
confidence: 99%
“…These institutional precautions also generate beyond‐compliance norms, which demand a commitment to norms that are derived from their status as professional regulators, particularly in handling conflicts of interest and avoiding using such offices for private gain (Lewis & Gilman, ; Stark, ). Past research has shown that not all ELOs perform these tasks equally well (van der Ven, , ). The temptation to create superficial eco‐labeling standards may be greater in GVCs characterized by unilateral governance (van der Ven, ).…”
Section: Novel Ethical Considerations For Gvc Membersmentioning
confidence: 99%